Higher education in Europe and the United States of America a diverse collection of essays - Wasser, Henry Hirsch 1919- (Univ. Press of America, 2007)
Abstract:. - http://www3.openu.ac.il/ouweb/owal/new_books1.book_desc?in_mis_cat=112808.